Economic Self-Efficacy and Economic Socialization: The Role of Psychological Resources in Shaping Economic Behavior - Nino Putkarashvili (European Research Materials, 2026)
The purpose of this study is to study the relationship between economic self-efficacy and economic socialization and to determine the role of economic self-efficacy in the process of forming economic behavior. Economic self-efficacy is considered as an individual’s belief in his or her own abilities in the context of successfully completing financial and economic tasks, and economic socialization is considered as a process through which a person acquires economic knowledge, values, skills and behavioral models. The empirical research data were processed in the program - SPSS. 528 respondents participated in the study. Descriptive statistics and Pearson correlation analysis were used for data analysis. The results showed that 45.6% of the respondents are characterized by a high level of economic self-efficacy, 45.5% - medium, and 8.9% - low. Correlation analysis revealed significant positive relationships between economic self-efficacy and financial independence (r = .635, p < .001), values ​​(r = .653, p < .001), psychological flexibility (r = .626, p < .001), financial knowledge (r = .552, p < .001), financial skills (r = .492, p < .001), and general self-efficacy (r = .532, p < .001). The results confirm that economic self-efficacy is one of the most important psychological mechanisms of economic socialization and has a significant impact on the formation of economic behavior. High economic self-efficacy is associated with financial activity, independent decision-making, effective management of financial resources, and economic independence. The results of the study emphasize the importance of developing economic self-efficacy in financial education and economic socialization programs as one of the key prerequisites for economic well-being and successful economic functioning.